The Polymorphic Nature of Violence and the Problem of its Significance - Romero Moñivas, Jesús (Razón y fe, 2025)
Violence is a historical, social and anthropological fact of a polymorphic and complex nature. The fundamental task of a scientific approach is to analyze violence as a phenomenon that can be explained and apprehended rationally, and not relegate it to the realm of the exceptional, immoral, pathological or irrational. The key is that violence is not a naked fact but is always crossed by meaning processes for the aggressor, the victim and the social context that encompasses them, influencing its typology and etiology and its intentionality and legitimacy. Therefore, violence is a behavioral strategy subject to interpretation in which conscious and unconscious elements, social and cultural dimensions, and cognitive and emotional processes are mixed, which invalidate any scientific interpretation or moral assessment that claims to be universal.
Keywords: violence; aggression; self-violence; violent intentionality; legitimized violence